Analytic Feynman Integral and a Change of Scale Formula for Wiener Integrals of an Unbounded Cylinder Function - Kim Young Sik (Complexity)
We investigate the behavior of the unbounded cylinder function Fx=∫0Tα1tdxt2k⋅∫0Tα2tdxt2k⋅⋯⋅∫0Tαntdxt2k, k=1,2,… whose analytic Wiener integral and analytic Feynman integral exist, we prove some relationships among the analytic Wiener integral, the analytic Feynman integral, and the Wiener integral, and we prove a change of scale formula for the Wiener integral about the unbounded function on the Wiener space C00,T.